2013
DOI: 10.1186/1471-2377-13-186
|View full text |Cite
|
Sign up to set email alerts
|

Cognition is only minimally impaired in Spinocerebellar ataxia type 14 (SCA14): a neuropsychological study of ten Norwegian subjects compared to intrafamilial controls and population norm

Abstract: BackgroundThere is an increasing awareness of the role of the cerebellum not only in motor, but also in cognitive and emotional functions. Spinocerebellar ataxia type 14 (SCA14) is an autosomal dominant hereditary ataxia characterized by a relatively pure cerebellar phenotype. Cognitive impairment has been reported in studies with phenotype descriptions of SCA14, but previous studies have been small without control groups, and no homogeneous and systematic test panel has been used. The objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(51 reference statements)
4
9
0
Order By: Relevance
“…In addition, cognitive impairment is only rarely reported in SCA14, and if cognition is affected, only minimal severity is reported, which was mirrored in our series. However, a formal neuropsychology assessment was conducted in symptomatic cases only limiting our ability to characterize this further.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, cognitive impairment is only rarely reported in SCA14, and if cognition is affected, only minimal severity is reported, which was mirrored in our series. However, a formal neuropsychology assessment was conducted in symptomatic cases only limiting our ability to characterize this further.…”
Section: Discussionsupporting
confidence: 78%
“…Comparison of the four patients in this case series highlights the distinct cognitive profiles associated with various subtypes of SCA, as supported by larger past studies [2, 3, 1927]. While some heterogeneity exists, there were some notable commonalities as well.…”
Section: Discussionsupporting
confidence: 77%
“…SCA14, the rarest of the four presented subtypes, has received very little attention with regard to the associated cognitive profile. The one case controlled study that has been reported found very little neurocognitive impairment in these patients [27]. Our patient, however, displayed notable deficits in visual memory, processing speed, and speeded phonemic fluency.…”
Section: Discussionmentioning
confidence: 42%
“…Executive dysfunction, however, is common to most of these profiles, consistent with disruption to frontal‐subcortical circuits. In those subtypes with more marked extracerebellar pathology (such as SCA1, 2, and 3), the cognitive deficits are also more pronounced than in those with more pure cerebellar involvement (e.g., SCA6 and late‐onset SCA14 cases) . Cognitive deterioration also parallels disease progression and/or correlates with disease severity, suggesting that these cognitive changes are integral to the disease .…”
Section: Cognitive Impairment Associated With “Primary” Movement Disomentioning
confidence: 99%
“…In those subtypes with more marked extracerebellar pathology (such as SCA1, 2, and 3), the cognitive deficits are also more pronounced than in those with more pure cerebellar involvement (e.g., SCA6 and late-onset SCA14 cases). 24,25 Cognitive deterioration also parallels disease progression and/or correlates with disease severity, suggesting that these cognitive changes are integral to the disease. [26][27][28] Although no studies have explicitly assessed whether these cognitive deficits contribute to the overall burden of disease, it is likely that these impairments are not just subclinical, and difficulties with planning, multitasking, and shifting are recognized by many patients and caregivers as affecting SCA patients' functional impairment.…”
Section: Genetic Ataxiasmentioning
confidence: 99%